Thick copper etching solution
By adding specific components to the thick copper etching liquid, the lateral and longitudinal etching anisotropy of the thick copper plate is solved, and the etching process of thick copper plates is improved, and the etching efficiency and product quality are improved.
Patent Information
- Application Number
- CN202411636987.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
AI Technical Summary
During the etching process of thick copper plates, as the thickness of the copper plate increases, the etching process becomes complicated and time-consuming, and the increase in lateral etching speed has an adverse impact on product quality and performance.
A thick copper etching liquid is used to contain hydrogen peroxide, inorganic acid, organic acid, hydrogen peroxide stabilizer, inorganic salt, hydroxyl-group small molecule surfactant and corrosion inhibitor. Through the combination of these components, the lateral and longitudinal etching can be achieved. The opposite sex reduces the lateral etching speed without affecting the longitudinal etching speed.
The full and effective etching of each part of the thick copper plate is achieved, ensuring that the etching morphology meets the requirements, controlling the etching rate and pattern key dimension loss, large etching capacity, and broad application prospects.
Smart Images

Figure CN119465153A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal etching, and in particular relates to a thick copper etching solution. Background Art
[0002] With the rapid progress of the electronics industry, electronic products are moving towards smaller and higher power density. This trend makes the heat dissipation problem of electronic products more critical, and new solutions are urgently needed. Thick copper plates are widely used in various fields such as aerospace, post and telecommunications, automatic control, and instrumentation due to their excellent thermal conductivity, electrical signal interference shielding ability, and excellent ultra-high voltage load.
[0003] However, the use of thick copper plates also brings new process challenges. As the thickness of the copper plates increases, the etching process becomes more complicated and time-consuming. Not only does the etching time increase accordingly, but the etching factor also gradually decreases. During the horizontal etching process, the etching liquid not only contacts the copper clad plate in the vertical direction, etching longitudinally, but also contacts the copper clad plate in the lateral direction, resulting in lateral etching. This lateral etching becomes more serious as the etching time increases, which may have an adverse effect on the quality and performance of the product.
[0004] CN117395880A discloses a method for etching a PCB board of ultra-thick copper, which relates to the technical field of printed circuit boards, and discloses the following steps: S1, substrate loading; S2, using an automatic laminator to press a 2.0 mils dry film on the copper surface of the substrate, and then using an exposure machine to expose; S3, using an acid etching solution to etch the substrate; S4, using an image transfer method to retain a layer of solder mask wet film at the position of the etched substrate; S5, using a graphic electrical process to tin the substrate; S6, using an alkaline etching SES line to remove the printed wet film, retaining the tin surface and the copper under the exposed wet film;
[0005] S7. Use alkaline etching line to etch away the exposed copper on the substrate until the exposed substrate surface meets the line width and line spacing requirements, while the copper protected by the tin surface is not etched. This etching method improves the uneven etching effect to a certain extent, but the operation steps are very complicated, which not only causes a huge waste of human resources, but also has a great impact on the equipment production capacity. Summary of the invention
[0006] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a thick copper etching solution, which realizes anisotropic etching in the horizontal and vertical directions, reduces the horizontal etching speed, but does not affect the vertical etching speed, so that all parts on the thick copper plate can be fully and effectively etched, not only can the etching morphology that meets the requirements be obtained, but also the etching rate and the key size loss of the pattern can be effectively controlled, the etching capacity is large, and the application prospect is relatively broad.
[0007] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:
[0008] A thick copper etching solution comprises the following components, measured by weight percentage: 10-20wt% hydrogen peroxide, 5-16wt% inorganic acid, 2-7wt% organic acid, 0.05-1wt% hydrogen peroxide stabilizer, 1-5wt% inorganic salt, 0.1-4wt% small molecule surfactant with hydroxyl group, 1-6wt% corrosion inhibitor, and the balance is deionized water.
[0009] Furthermore, the preparation method of the corrosion inhibitor comprises the following steps:
[0010] Step (1), adding N5-phenyl-1H-1,2,4-thiazole-3,5-diamine to isopropanol, then adding 4-acetamidobenzenesulfonyl chloride, stirring evenly, stirring and reacting at 35-45° C. for 1-3 hours, adding deionized water, stirring, crystallizing, filtering, drying, and recrystallizing from methanol / ether to obtain an intermediate, the reaction formula is as follows:
[0011]
[0012] Step (2), dissolving the intermediate in tetrahydrofuran, slowly adding an ethanol solution containing citronellal dropwise within 3-5 minutes, heating under reflux at 75-85° C. for 2-3 hours, cooling to room temperature, distilling off the solvent under reduced pressure, filtering, drying, and recrystallizing with ether to obtain a corrosion inhibitor, the reaction formula is as follows:
[0013]
[0014] Furthermore, in step (1), the ratio of the amount of N5-phenyl-1H-1,2,4-thiazole-3,5-diamine, p-acetamidobenzenesulfonyl chloride and isopropanol is (1.7-2.0) g:(2.3-2.7) g:50 mL.
[0015] Furthermore, in step (2), the ratio of the intermediate, the ethanol solution of citronellal, and tetrahydrofuran is (3.0-3.2) g: (20-25) g: 50 mL.
[0016] Furthermore, in the ethanol solution of citronellal, the mass content of citronellal is 5.25-6.25wt%.
[0017] Furthermore, the inorganic acid is one or more of nitric acid, sulfuric acid and hydrochloric acid.
[0018] Furthermore, the organic acid is one or more of arginine, histidine, aspartic acid, ascorbic acid, mandelic acid, malic acid, citric acid, and tartaric acid.
[0019] Furthermore, the hydrogen peroxide stabilizer is one or more of urea, phenylurea, allyl urea, 1,3-dimethyl urea, thiourea, phenylacetamide, and phenyl glycol.
[0020] Furthermore, the inorganic salt is one or more of sodium sulfate, potassium sulfate, sodium chloride, potassium chloride, sodium bisulfate, potassium nitrate, ammonium nitrate, sodium nitrate, sodium dihydrogen phosphate, and ammonium sulfate.
[0021] Furthermore, the small molecule surfactant with hydroxyl group is one or more of lauryl alcohol, tetradecanol, hexadecanol, stearyl alcohol, glycerol monooleate, sorbitan laurate, N,N-di(hydroxyethyl)cocamide, and trimethylolpropane cocoate.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention provides a thick copper etching solution, which is prepared by mixing hydrogen peroxide, inorganic acid, organic acid, hydrogen peroxide stabilizer, inorganic salt, small molecule surfactant with hydroxyl group, corrosion inhibitor, and the balance of deionized water. The solution realizes anisotropic etching in the horizontal and vertical directions, reduces the horizontal etching speed, but does not affect the vertical etching speed, so that all parts of the thick copper plate can be fully and effectively etched, and the etching factors can meet the use requirements. Specifically, the thick copper etching solution provided by the present invention is applied to the etching process of the thick copper plate, not only can the etching morphology that meets the requirements be obtained, but also the etching rate and the key size loss of the pattern can be effectively controlled, the etching capacity is large, and the application prospect is relatively broad.
[0024] 2. The present invention provides a corrosion inhibitor for thick copper etching solution. First, the sulfur-chlorine bond in 4-acetamidobenzenesulfonyl chloride is used to react with the hydrogen connected to the imino group on the nitrogen ring in N5-phenyl-1H-1,2,4-thiazole-3,5-diamine to undergo a nucleophilic substitution reaction to form a sulfonamide bond to obtain an intermediate; then, the primary amine group of the intermediate reacts with the active carbonyl group of citronellal in a mixed solvent of tetrahydrofuran and ethanol to undergo a Schiff base reaction to obtain a corrosion inhibitor; the microstructure of the corrosion inhibitor obtained by the present invention is a T-shaped structure, which is vertically laid on the copper surface, and the lone pair electrons of N, O, and S heteroatoms and the large π of the benzene ring exist in the intermediate part. The π-π bond of the thiazole ring can combine with the empty orbital of the copper atom to form a stable complex of Cu(Ⅰ) or Cu(Ⅱ) ions on the copper surface, forming a more stable and denser protective film, thereby more effectively preventing or slowing down the corrosion of the metal; at the same time, the hydrocarbon group of citronellal can play a hydrophobic role, effectively preventing the corrosion medium from diffusing to the copper surface and thus inhibiting corrosion; and the hydrocarbon group has a positive inductive effect, which can enhance the electron exchange between the corrosion inhibitor and the copper surface, thereby promoting the adsorption of the corrosion inhibitor on the copper surface, reducing the corrosion rate of the etching solution on the copper surface, reducing the lateral etching rate, increasing the etching factor, and uniformly corroding.
[0025] 3. The present invention adds a small molecule surfactant with hydroxyl groups to the thick copper etching solution. On the one hand, it is to reduce the surface tension of the etching solution so that it can better infiltrate the copper surface and increase the etching rate; on the other hand, the addition of the small molecule surfactant with hydroxyl groups can produce a synergistic effect with the corrosion inhibitor in the etching solution, increase the adsorption amount of the acid etching solution additive on the copper surface, enhance the corrosion inhibition effect of the acid etching solution additive, and improve the etching factor. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0027] Figure 1 is the hydrogen nuclear magnetic resonance spectrum of the intermediate provided in Preparation Example 1 of the present invention;
[0028] Figure 2 is the nuclear magnetic resonance hydrogen spectrum of the corrosion inhibitor provided in Preparation Example 1 of the present invention;
[0029] Figure 3 This is a planar SEM image of the copper sample provided in the performance test of the present invention;
[0030] Figure 4 This is a planar SEM image of a copper sample etched by the thick copper etching solution provided in Example 1 of the performance test of the present invention;
[0031] Figure 5 This is a plane SEM image of a copper sample etched by the thick copper etching solution provided in Comparative Example 1 in the performance test of the present invention;
[0032] Figure 6 This is a planar SEM image of a copper sample etched with the thick copper etching solution provided in Comparative Example 2 in the performance test of the present invention;
[0033] Figure 7 This is a plane SEM image of a copper sample etched with the thick copper etching solution provided in Comparative Example 3 in the performance test of the present invention;
[0034] Figure 8 This is a planar SEM image of a copper sample etched with the thick copper etching solution provided in Comparative Example 4 in the performance test of the present invention;
[0035] Fig. 9 This is a planar AFM image of a copper sample after etching with the thick copper etching solution provided in Example 1 of the performance test of the present invention;
[0036] Fig.10 This is a planar AFM image of a copper sample after etching with the thick copper etching solution provided in Comparative Example 4 in the performance test of the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Preparation Example 1-3 provides a method for preparing a corrosion inhibitor.
[0039] Preparation Example 1
[0040] This preparation example provides a method for preparing a corrosion inhibitor, comprising the following steps:
[0041] Step (1), adding 1.75g N5-phenyl-1H-1,2,4-thiazole-3,5-diamine to 50mL isopropanol, then adding 2.33g 4-acetamidobenzenesulfonyl chloride, stirring evenly, stirring and reacting at 35°C for 1h, adding 50mL deionized water, stirring, crystallization, suction filtration, drying at 80°C for 2h, and recrystallization with 100mL methanol / ether (volume ratio of 2:1) to obtain 3.35g product; the product was measured by HPLC-MS, m / z=372.1, confirming that the product is an intermediate, and based on this standard, the yield of the reaction was 90.05%; and the intermediate was measured by hydrogen nuclear magnetic resonance spectrum as follows Figure 1 As shown, hydrogen spectrum analysis: 1H NMR (500MHz, CHCl3) δ9.41 (s, 1H), 8.62 (s, 1H), 8.15-8.11 (m, 2H), 7.70-7.61 (m, 4H), 7.24 (dd, J = 7.6, 6.9 Hz, 2H), 7.03 (s, 1H), 6.67 (d, J = 8.1 Hz, 1H), 6.54 (s, 1H), 2.16 (s, 3H); Figure 1 The total number of hydrogen integrals is 9, of which the peak at 2.16 is the leftmost terminal methyl peak of the intermediate;
[0042] Step (2), 3.01g of the intermediate was dissolved in 50mL of tetrahydrofuran, 20g of an ethanol solution containing citronellal (the mass content of citronellal was 6.15wt%) was slowly added dropwise, and the addition was completed within 3min, and the reaction was heated to reflux at 75°C for 2h, cooled to room temperature, the solvent was evaporated under reduced pressure, filtered, dried at 80°C for 2h, and recrystallized from 100mL of ether to obtain 3.42g of product; HPLC-MS of the product was measured, m / z=508.2, confirming that the product was a corrosion inhibitor, and the yield of the reaction was calculated based on this standard, and the corrosion inhibitor was measured by hydrogen nuclear magnetic resonance spectrum as follows: Figure 2As shown; hydrogen spectrum analysis: 1H NMR (500MHz, CHCl3) δ9.41 (s, 1H), 8.16-8.09 (m, 1H), 7.73-7.66 (m, 1H), 7.65-7.60 (m, 1H), 7.26-7.21 (m, 1H), 7.03 (tt, J = 7.0, 1.2Hz, 1H), 5.08 (tdt, J = 6.4 , 2.7, 1.5Hz, 1H), 2.41-2.26 (m, 1H), 2.06-1.95 (m, 1H), 1.62 (ddt, J=13.2, 2.4 , 1.2Hz, 3H), 1.46 (ddtd, J=43.0, 12.6, 7.9, 6.9Hz, 1H), 0.94 (d, J=6.6Hz, 2H); Figure 2 The total number of hydrogen integrals is 16, which is consistent with the number of hydrogen atoms in the target product, and the peak at 7.92 is the absorption peak of the hydrogen atom on the C=N bond of the corrosion inhibitor.
[0043] Preparation Example 2
[0044] This preparation example provides a method for preparing a corrosion inhibitor, comprising the following steps:
[0045] Step (1), adding 1.85 g of N5-phenyl-1H-1,2,4-thiazole-3,5-diamine to 50 mL of isopropanol, and then adding 2.43 g of 4-acetamidobenzenesulfonyl chloride, stirring evenly, stirring and reacting at 40° C. for 2 h, adding 50 mL of deionized water, stirring, crystallization, suction filtration, drying at 80° C. for 2.5 h, and recrystallization with 100 mL of methanol / ether (volume ratio of 2:1) to obtain 3.56 g of product; HPLC-MS of the product, m / z=372.1, confirming that the product is an intermediate, and based on this standard for calculation, the yield of the reaction is 91.74%;
[0046] Step (2), dissolving 3.15 g of the intermediate in 50 mL of tetrahydrofuran, slowly adding dropwise 22 g of an ethanol solution of citronellal (the mass content of citronellal is 6.00 wt%), the addition is completed within 4 min, heating to reflux at 80 ° C for 2.5 h, cooling to room temperature, distilling off the solvent under reduced pressure, filtering, drying at 80 ° C for 2.5 h, and recrystallizing with 100 mL of ether to obtain 3.61 g of product; HPLC-MS of the product, m / z=508.2, confirming that the product is a corrosion inhibitor, and calculating based on this standard, the yield of the reaction is 83.91%.
[0047] Preparation Example 3
[0048] This preparation example provides a method for preparing a corrosion inhibitor, comprising the following steps:
[0049] Step (1), adding 2.01 g of N5-phenyl-1H-1,2,4-thiazole-3,5-diamine to 50 mL of isopropanol, and then adding 2.69 g of 4-acetamidobenzenesulfonyl chloride, stirring evenly, stirring and reacting at 45° C. for 3 h, adding 50 mL of deionized water, stirring, crystallization, suction filtration, drying at 80° C. for 3 h, and recrystallization with 100 mL of methanol / ether (volume ratio of 2:1) to obtain 3.86 g of product; HPLC-MS of the product was measured, m / z=372.1, confirming that the product is an intermediate, and based on this standard, the yield of the reaction was 90.32%;
[0050] Step (2), 3.19g of the intermediate was dissolved in 50mL of tetrahydrofuran, 25g of an ethanol solution containing citronellal (the mass content of citronellal is 5.28wt%) was slowly added dropwise within 5min, the reaction was heated to reflux at 85°C for 3h, cooled to room temperature, the solvent was evaporated under reduced pressure, filtered, dried at 80°C for 3h, and recrystallized from 100mL of ether to obtain 3.55g of product; HPLC-MS of the product was measured, m / z=508.2, confirming that the product was a corrosion inhibitor, and the yield of the reaction was 81.50% based on this standard.
[0051] Examples 1-5 and Comparative Examples 1-4 provide a thick copper etching solution.
[0052] Example 1
[0053] The present embodiment provides a thick copper etching solution, which includes the following components by weight percentage: 18wt% hydrogen peroxide, 10wt% inorganic acid, 5wt% organic acid, 0.5wt% hydrogen peroxide stabilizer, 2.5wt% inorganic salt, 2.5wt% small molecule surfactant with hydroxyl group, 5wt% corrosion inhibitor, and the balance is deionized water;
[0054] Among them, the inorganic acid is obtained by mixing nitric acid and hydrochloric acid in a mass ratio of 1:1; the organic acid is arginine; the hydrogen peroxide stabilizer is phenyl urea; the inorganic salt is sodium chloride; the small molecule surfactant with hydroxyl group is lauryl alcohol; and the corrosion inhibitor is prepared by Preparation Example 1.
[0055] Example 2
[0056] The present embodiment provides a thick copper etching solution, which includes the following components by weight percentage: 10wt% hydrogen peroxide, 16wt% inorganic acid, 7wt% organic acid, 0.05wt% hydrogen peroxide stabilizer, 5wt% inorganic salt, 0.1wt% small molecule surfactant with hydroxyl group, 6wt% corrosion inhibitor, and the balance is deionized water;
[0057] Among them, the inorganic acid is obtained by mixing sulfuric acid and hydrochloric acid in a mass ratio of 1:1; the organic acid is mandelic acid; the hydrogen peroxide stabilizer is obtained by mixing urea and phenyl glycol in a mass ratio of 2:1; the inorganic salt is sodium sulfate; the small molecule surfactant with hydroxyl group is N,N-di(hydroxyethyl)cocamide; and the corrosion inhibitor is prepared by Preparation Example 2.
[0058] Example 3
[0059] The present embodiment provides a thick copper etching solution, which includes the following components by weight percentage: 20wt% hydrogen peroxide, 5wt% inorganic acid, 2wt% organic acid, 1wt% hydrogen peroxide stabilizer, 1wt% inorganic salt, 4wt% small molecule surfactant with hydroxyl group, 1wt% corrosion inhibitor, and the balance is deionized water;
[0060] Among them, the inorganic acid is nitric acid; the organic acid is obtained by mixing malic acid and tartaric acid in a mass ratio of 1:1; the hydrogen peroxide stabilizer is 1,3-dimethylurea; the inorganic salt is ammonium nitrate; the small molecule surfactant with hydroxyl group is trimethylolpropane cocoate; and the corrosion inhibitor is prepared by Preparation Example 3.
[0061] Example 4
[0062] The present embodiment provides a thick copper etching solution, which includes the following components by weight percentage: 18wt% hydrogen peroxide, 10wt% inorganic acid, 5wt% organic acid, 0.5wt% hydrogen peroxide stabilizer, 2.5wt% inorganic salt, 2.5wt% small molecule surfactant with hydroxyl group, 5wt% corrosion inhibitor, and the balance is deionized water;
[0063] Among them, the inorganic acid is obtained by mixing nitric acid and hydrochloric acid in a mass ratio of 1:1; the organic acid is arginine; the hydrogen peroxide stabilizer is phenyl urea; the inorganic salt is sodium chloride; the small molecule surfactant with hydroxyl group is glycerol monooleate; and the corrosion inhibitor is prepared by Preparation Example 1.
[0064] Example 5
[0065] The present embodiment provides a thick copper etching solution, which includes the following components by weight percentage: 18wt% hydrogen peroxide, 10wt% inorganic acid, 5wt% organic acid, 0.5wt% hydrogen peroxide stabilizer, 2.5wt% inorganic salt, 2.5wt% small molecule surfactant with hydroxyl group, 5wt% corrosion inhibitor, and the balance is deionized water;
[0066] Among them, the inorganic acid is obtained by mixing nitric acid and hydrochloric acid in a mass ratio of 1:1; the organic acid is arginine; the hydrogen peroxide stabilizer is phenyl urea; the inorganic salt is sodium chloride; the hydroxyl-containing small molecule surfactant is obtained by mixing lauryl alcohol and glycerol monooleate in a mass ratio of 1:1; and the corrosion inhibitor is prepared by Preparation Example 1.
[0067] Comparative Example 1
[0068] This comparative example provides a thick copper etching solution, which is different from Example 1 only in that the corrosion inhibitor is 2-mercaptobenzothiazole, specifically as follows:
[0069] A thick copper etching solution comprises the following components by weight percentage: 18wt% hydrogen peroxide, 10wt% inorganic acid, 5wt% organic acid, 0.5wt% hydrogen peroxide stabilizer, 2.5wt% inorganic salt, 2.5wt% small molecule surfactant with hydroxyl group, 5wt% corrosion inhibitor, and the balance is deionized water;
[0070] Among them, the inorganic acid is obtained by mixing nitric acid and hydrochloric acid in a mass ratio of 1:1; the organic acid is arginine; the hydrogen peroxide stabilizer is phenyl urea; the inorganic salt is sodium chloride; the small molecule surfactant with hydroxyl group is lauryl alcohol; and the corrosion inhibitor is 2-mercaptobenzothiazole.
[0071] Comparative Example 2
[0072] This comparative example provides a thick copper etching solution, which is different from Example 1 only in that an equal mass of sodium dodecylbenzene sulfonate is used to replace the small molecule surfactant with a hydroxyl group, specifically as follows:
[0073] A thick copper etching solution comprises the following components by weight percentage: 18wt% hydrogen peroxide, 10wt% inorganic acid, 5wt% organic acid, 0.5wt% hydrogen peroxide stabilizer, 2.5wt% inorganic salt, 2.5wt% sodium dodecylbenzene sulfonate, 5wt% corrosion inhibitor, and the balance is deionized water;
[0074] The inorganic acid is obtained by mixing nitric acid and hydrochloric acid in a mass ratio of 1:1; the organic acid is arginine; the hydrogen peroxide stabilizer is phenylurea; the inorganic salt is sodium chloride; and the corrosion inhibitor is obtained by Preparation Example 1.
[0075] Comparative Example 3
[0076] This comparative example provides a thick copper etching solution, which is different from Example 1 only in that an equal mass of corrosion inhibitor is used to replace the small molecule surfactant with hydroxyl group, as follows:
[0077] A thick copper etching solution comprises the following components by weight percentage: 18wt% hydrogen peroxide, 10wt% inorganic acid, 5wt% organic acid, 0.5wt% hydrogen peroxide stabilizer, 2.5wt% inorganic salt, 7.5wt% corrosion inhibitor, and the balance is deionized water;
[0078] The inorganic acid is obtained by mixing nitric acid and hydrochloric acid in a mass ratio of 1:1; the organic acid is arginine; the hydrogen peroxide stabilizer is phenylurea; the inorganic salt is sodium chloride; and the corrosion inhibitor is obtained by Preparation Example 1.
[0079] Comparative Example 4
[0080] This comparative example provides a thick copper etching solution, which is different from Example 1 only in that an equal mass of a small molecule surfactant with a hydroxyl group is used to replace the corrosion inhibitor, specifically as follows:
[0081] A thick copper etching solution comprises the following components by weight percentage: 18wt% hydrogen peroxide, 10wt% inorganic acid, 5wt% organic acid, 0.5wt% hydrogen peroxide stabilizer, 2.5wt% inorganic salt, 7.5wt% small molecule surfactant with hydroxyl group, and the balance is deionized water;
[0082] The inorganic acid is obtained by mixing nitric acid and hydrochloric acid in a mass ratio of 1:1; the organic acid is arginine; the hydrogen peroxide stabilizer is phenyl urea; the inorganic salt is sodium chloride; and the small molecule surfactant with a hydroxyl group is lauryl alcohol.
[0083] Performance Testing
[0084] The thick copper etching solution provided in the above embodiment and comparative example was tested for performance, and the relevant test items and test process are as follows:
[0085] Take a thick copper printed circuit test board with a size of 330mm×440mm, a copper thickness of 105μm, and a board thickness of 1.5mm, and perform glue filling, polishing, and etching. The upper and lower spray pressures during the etching process are 2.5kg / cm 2 , 2.0kg / cm 2 , speed is 6.0m / min, temperature is 30℃, and time is 60s.
[0086] Etching factor: Use SEM to observe the cross-section of the circuit on the test piece, the line bottom and line top width, and calculate the etching factor. The etching factor adopts the industry standard: copper thickness / [2×(line bottom-line top)].
[0087] Roughness: SEM and AFM were used to observe the planar etching of the copper samples after etching with the thick copper etching solution obtained in Examples 1-5 and Comparative Examples 1-4, and the values of Ra and Rq in AFM were recorded; wherein, Figure 3 This is the original plane SEM image of the copper sample; Figure 4-8 The planar SEM images of the copper samples etched by the thick copper etching solutions obtained in Example 1 and Comparative Examples 1-4 are shown respectively; Fig. 9 , 10 The planar AFM images of the copper samples after etching with the thick copper etching solution obtained in Example 1 and Comparative Example 4 are respectively;
[0088] The test results are shown in Table 1;
[0089] Table 1
[0090]
[0091]
[0092] It can be seen from Table 1 that, by comparing the data of Example 1 and Comparative Example 1, the corrosion inhibitor in Comparative Example 1 uses 2-mercaptobenzothiazole, indicating that the corrosion inhibitor prepared by the present invention has better corrosion inhibition effect than 2-mercaptobenzothiazole, which is beneficial to improving the etching factor, and the obtained thick copper sample surface has smaller grains and less roughness; it can be seen from the data of Example 1 and Comparative Example 2 in the table that the small molecule surfactant with hydroxyl groups helps to improve the thick copper etching solution and improve the etching factor, and the etching of the thick copper sample surface is uniform; it can be seen from the data of Example 1, Comparative Examples 3 and 4 in the table that the synergistic effect of the corrosion inhibitor prepared by the present invention and the small molecule surfactant with hydroxyl groups interacts more strongly with the copper surface, is not easy to desorb, has a better effect of slowing down the etching rate, and the obtained copper surface grains are smaller and denser, and the flatness is better.
[0093] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0094] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A thick copper etching solution, characterized in that: According to weight percentage, it includes the following ingredients: 10-20wt% hydrogen peroxide, 5-16wt% inorganic acid, 2-7wt% organic acid, 0.05-1wt% hydrogen peroxide stabilizer, 1-5wt% inorganic salt, 0.1-4wt% small molecule surfactant with hydroxyl group, 1-6wt% corrosion inhibitor, and the balance is deionized water.
2. A thick copper etching solution according to claim 1, characterized in that: The preparation method of the corrosion inhibitor comprises the following steps: Step (1), adding N5-phenyl-1H-1,2,4-thiazole-3,5-diamine to isopropanol, then adding 4-acetamidobenzenesulfonyl chloride, stirring evenly, stirring and reacting at 35-45° C. for 1-3 hours, adding deionized water, stirring, crystallizing, filtering, drying, and recrystallizing from methanol / ether to obtain an intermediate; Step (2), dissolving the intermediate in tetrahydrofuran, slowly adding an ethanol solution containing citronellal dropwise within 3-5 minutes, heating under reflux at 75-85° C. for 2-3 hours, cooling to room temperature, distilling off the solvent under reduced pressure, filtering, drying, and recrystallizing with ether to obtain a corrosion inhibitor.
3. A thick copper etching solution according to claim 2, characterized in that: In step (1), the ratio of the amount of N5-phenyl-1H-1,2,4-thiazole-3,5-diamine, p-acetamidobenzenesulfonyl chloride and isopropanol is (1.7-2.0) g:(2.3-2.7) g:50 mL.
4. A thick copper etching solution according to claim 2, characterized in that: In step (2), the ratio of the intermediate, the ethanol solution of citronellal and tetrahydrofuran is (3.0-3.2) g: (20-25) g: 50 mL.
5. A thick copper etching solution according to claim 2, characterized in that: In the ethanol solution of citronellal, the mass content of citronellal is 5.25-6.25wt%.
6. A thick copper etching solution according to claim 1, characterized in that: The inorganic acid is one or more of nitric acid, sulfuric acid and hydrochloric acid.
7. A thick copper etching solution according to claim 1, characterized in that: The organic acid is one or more of arginine, histidine, aspartic acid, ascorbic acid, mandelic acid, malic acid, citric acid and tartaric acid.
8. A thick copper etching solution according to claim 1, characterized in that: The hydrogen peroxide stabilizer is one or more of urea, phenylurea, allyl urea, 1,3-dimethyl urea, thiourea, phenylacetamide, and phenyl glycol.
9. A thick copper etching solution according to claim 1, characterized in that: The inorganic salt is one or more of sodium sulfate, potassium sulfate, sodium chloride, potassium chloride, sodium bisulfate, potassium nitrate, ammonium nitrate, sodium nitrate, sodium dihydrogen phosphate, and ammonium sulfate.
10. A thick copper etching solution according to claim 1, characterized in that: The small molecule surfactant with hydroxyl group is one or more of lauryl alcohol, tetradecanol, hexadecanol, stearyl alcohol, glycerol monooleate, sorbitan laurate, N,N-di(hydroxyethyl)cocamide, and trimethylolpropane cocoate.
Citation Information
Patent Citations
Ultra-thick copper PCB etching method
CN117395880A